Foreign investment & growth in emerging economies: panel ARDL analysis - Michael Appiah; Fanglin Li; Benjamin Korankye (Journal of Economics, Business, and Accountancy Ventura, 2019)
Recently, the contributory role of foreign investment growth in Africa has been considered by researchers and policymakers. Studies in this area are not yet clear. Besides, foreign direct investment has emerged as a determining factor of economic growth. Concerning this evidence, the current study tries to investigate the contributions of foreign direct investment on economic growth or for developing the economy of Africa. This study used yearly panel data for the period 1995-2015 for 5 developing the economy of Africa. The results of Panel ARDL indicate that foreign direct investment has a positive effect on economic growth as well as a positive sign of trade openness, inflation, and labor. The study also stresses that, for increasing economic growth, there is a need to seek more foreign investments, increase trade openness and inflation, and at the same time, to improve the employment condition in the selected African developing countries.